2013
DOI: 10.1016/j.febslet.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure of human, Drosophila melanogaster and Caenorhabditis elegans MFE‐2 in solution from synchrotron small‐angle X‐ray scattering

Abstract: Edited by Christian GriesingerKeywords: Peroxisome b-Oxidation Multifunctional enzyme type 2 Sterol carrier protein 2-like Synchrotron a b s t r a c t Multifunctional enzyme type 2 (MFE-2) forms part of the fatty acid b-oxidation pathway in peroxisomes. MFE-2s from various species reveal proteins with structurally homologous functional domains assembled in different compilations. Crystal structures of all domain types are known. SAXS data from human, fruit fly and Caenorhabditis elegans MFE-2s and their consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In yeast or mammalian cells, matrix proteins targeted to peroxisomes via the PTS1 pathway rely on the receptor Pex5 for their import. D‐Bifunctional protein (DBP) is an enzyme with oxidoreductase activity that is involved in the β‐oxidation of very‐long chain fatty acids . DBP contains the PTS1 signal ‐AKL, and RFP‐DBP strongly colocalizes (76.2%) with peroxisomes in S2 cells (Figures B and ).…”
Section: Resultsmentioning
confidence: 99%
“…In yeast or mammalian cells, matrix proteins targeted to peroxisomes via the PTS1 pathway rely on the receptor Pex5 for their import. D‐Bifunctional protein (DBP) is an enzyme with oxidoreductase activity that is involved in the β‐oxidation of very‐long chain fatty acids . DBP contains the PTS1 signal ‐AKL, and RFP‐DBP strongly colocalizes (76.2%) with peroxisomes in S2 cells (Figures B and ).…”
Section: Resultsmentioning
confidence: 99%
“…This extra domain is not present in yeast ECI2 and its function in mammalian ECI2 is not clear. Such an extra lipid‐molecule binding domain of unknown function is also found in some other peroxisomal enzymes, such as in the mammalian sterol carrier protein type 2 (SCP2) thiolase (having an extra SCP2 domain) and in peroxisomal multifunctional enzyme type 2 (MFE2) (also having an SCP2 domain) . A common structural feature of every crotonase enzyme is helix‐10.…”
Section: Introductionmentioning
confidence: 99%
“…Several other predicted proteins had a variant PTS1 at their C-terminus, suggesting they also localized to peroxisomes (Faust et al, 2012). One predicted L-bifunctional protein, CG3415, had its quaternary structure resolved by X-ray scattering and was found to be very similar to that of human MFE-2, a known peroxisomal β-oxidation enzyme (Mehtala et al, 2013). A comprehensive screen of all predicted Drosophila peroxisomal proteins by Baron et al (2016) found the most putative β-oxidation enzyme homologs identified by Faust et al (2012) were greater than 75% co-localized with the peroxisome marker GFP-PTS1.…”
Section: Lipid Oxidationmentioning
confidence: 99%